Employee loyalty and organizational performance: a critical survey. Issue 5 (11th August 2014) - Guillon, Olivia; Cezanne, Cécile
Abstract : Purpose: – The purpose of this paper is to clarify the relationship between employee loyalty and organizational performance. It starts with the idea that the employee loyalty creates value for the organization. This statement is widely endorsed in the literature although there is little consensus on the definition of loyalty. The paper proposes a refined synthesis of the literature on the link between employee loyalty and organizational performance. Design/methodology/approach: – The paper addresses the question of whether there is a robust positive link between employee loyalty and organizational performance. The paper starts by reviewing the various, sometimes divergent, approaches to employee loyalty in the literature and then compare the different indicators of loyalty in relation to their relevance to different indicators of performance. Findings: – The paper provides a critical overview of the different existing conceptions of employee loyalty. It points out ambiguity about both the theoretical contours of the concept, and practical means of making it a source of value for the organization. The paper shows that the link between employee loyalty and performance varies according to the type of indicators used. Research limitations/implications: – The paper highlights a variety of indicators for employee loyalty to their firm and for organizational performance. But much research remains to be conducted, notably on the managerial levers that might consolidate or improve organizational performance. Originality/value: – This paper fulfills an identified need to survey a fragmented theoretical field of analysis.